Potassium Ion Channel Protein (KCNH) Levels in Patients with Fibromyalgia Syndrome - Tas, Ayca; Hayta, Emrullah; Karadag, Ahmet; Zontul, Cemile; Ozmen, Esma; Aydin, Suleyman; Silig, Yavuz (C M B Assoc, 2021)
Although there is not yet full clarity of the pathogenesis of fibromyalgia syndrome (FM), central sensitization is considered to be responsible. The purpose of this study was to measure the plasma levels of potassium ion channel proteins (human KCNH2, KCNH6 and KCNH7) in FM patients and healthy control subjects. The study sample includes 76 newly diagnosed FM patients and 79 healthy individuals. Venous blood samples were taken to measure the plasma levels of KCNH2, KCNH6 and KCNH7. Pain severity in FM patients was assessed using a visual analog scale (VAS). Bioinformatics analysis was performed using the STRING v 11 Protein interaction tool. Age, gender and body mass index were seen to be similar in both groups. In comparisons between FM and control groups, KCNH2 plasma levels was found to be significantly lower in the FM group. No significant correlation was found between plasma levels of KCNH2, KCNH6 and KCNH7 protein levels and VAS score of patients with FM. The KCNH2 protein had a high homology score with 9 proteins. The plasma levels of KCNH2 FM patients were found to be lower than those of the healthy control subjects, no difference was determined in respect of the plasma levels of KCNH6 and KCNH7. These results may be of use in guiding future studies on the pathogenesis of FM. Copyright: (c) 2021 by the C.M.B. Association. All rights reserved.
Keywords: Potassium ion channel; fibromyalgia; KCNH2, KCNH6 and KCNH7